Training für Verbesserung der Ausdauer - Richards, R.
Training for aerobic improvements is described. Contents are: - The aerobic capacity, - Aerobic Power or Aerobic Capacity - What's the Difference? - Training to Improve Aerobic Capacity and Power (Are there critical periods of development when aerobic training can be used to best affect? What volume of training should be devoted to aerobic work? What training intensity is best employed to improve aerobic potential?) Summary: Improvement in aerobic capacity is a desirable training goal for the development of swimming endurance and overall ability to absorb a variety of training stimuli. The concomitant goal of improving aerobic power may also be achieved through the prescription of training loads that represent as little as 60% (for unfit or novice swimmers) to 85-90% (fit swimmers) of maximum capacity. The resulting adaptations that occur produce a shift in the swimming velocity required at one's 'individual anaerobic threshold' (i.e. threshold speed becomes progressively faster). A greater percentage of aerobic capacity becomes available for sub-maximal performance, thereby improving energy efficiency through a range of swimming speeds. Programs that regularly require maximum aerobic capacity training loads do not seem to be warranted for prepubertal swimmers. Progressive loading of both training volume and submaximal intensities will produce the desired aerobic improvements. However, senior age-group and/or elite swimmers may effectively use training sets designed to elicit a maximum aerobic load. Whenever maximum aerobic training loads are used, there must be sufficient recovery (i.e. adjusting the intensity of other training stimuli to act as active recovery) between applications in the training cycle.